Outcome analysis of intussusception in fifty children at a tertiary centre in Mumbai - Dr Charu Tiwari; Dr Gursev Sandlas; Dr Shalika Jayaswal; Dr Hemanshi Shah (Pediatric Review: International Journal of Pediatric Research, 2015)
Background: Intussusception is a common cause of obstruction in Paediatric patients. Recognizing and treating this condition rapidly is important to prevent potentially fatal complications. Methods: Fifty consecutive patients of intussusception were analyzed with respect to age, presenting symptoms with duration, laboratory and radiological findings, type of management, duration of hospital stay and follow-up. Results: The median age at presentation was 11 months. Patients presenting between 3 months and 2 years of age are more likely to require operative intervention. The most common presenting symptoms were abdominal pain and vomiting. The diagnosis of intussusception was made by Ultrasonography and a trial of non-operative intervention was given first by in the form of USG guided hydrostatic reduction. Most of the patients required two or lesser attempts of reduction and were thus managed non-operatively. Those who did not respond to 2 or more attempts of hydrostatic reduction required operative intervention and all of these had some or the other lead point. Eight out of 11 operated patients (72.72%) required resection for the gangrenous bowel segment. The most common type of intussusception was ileo-colic and most of them were idiopathic. Lead points were found in all the patients who were operated; the most common being enlarged mesenteric lymph nodes. Conclusion: Children presenting between 3 months to 2 years of age, with no palpable abdominal lump or passage of red currant jelly-like stools as symptoms and getting reduced hydrostatically at one or two attempts mostly have idiopathic intussusception and such patients won’t require operative intervention.